Analisis Perkembangan UMKM Sektor Kuliner Di Kota Malang - Safira, Annisa Ayu; Nurhidayah, Nurhidayah; Saraswati, Ety (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The food industry in Malang City has been growing rapidly. Food vendors can be found in almost every area, indicating a high demand in this sector. Culinary MSME actors offer a variety of flavors to attract consumers who are constantly seeking new products. People also tend to purchase their food needs from local vendors. This rapid development is further driven by the city’s dense population. The research problems in this study are: 1) How do Information Technology, Business Capital, and Financial Reporting influence the development of culinary MSMEs in Malang City? 2) How can Information Technology enhance the development of culinary MSMEs in Malang City? 3) How can Business Capital enhance the development of culinary MSMEs in Malang City? 4) How can Financial Reporting enhance the development of culinary MSMEs in Malang City? The research method applied is qualitative research using NVIVO as the analytical tool. The results of the study show that: 1) The use of Information Technology by culinary MSMEs in Malang City contributes significantly to improving operational efficiency, 2) The business capital used by culinary MSMEs in Malang City is partly sourced from personal funds, 3) The financial reports prepared by culinary MSMEs in Malang City generally include the basic information required, although they are not yet detailed and comprehensive, 4) The business duration of the eight culinary MSME actors in Malang City varies, with some experiencing long-term sustainability while others face short-term business endurance. Keywords: MSME Development, Culinary